Uso de mapas históricos na pesquisa sobre a cidade de São Paulo. Predominância de mapas disponíveis digitalmente e mapas autorreferenciais - Eliane Kuvasney (Confins)
Two questions triggered this research: From the moment that maps are considered historical sources, how are they chosen and used as sources? Do the narratives that deal with space and spatialities of the past out of Geography and the map do so from a set of cartographic documents that are not very diverse? It was observed, from a survey in the thesis bank of the University of São Paulo and surveys in the physical collections of public archives, that some easily accessible maps - because they were made available digitally - were naturalized, in the sense that they are treated as the truth of the territory within the periods in which they were produced and that others - absent from digital archives - can provide us with other narratives that are distant from that produced by the naturalization of cartographic series present in our imagination since before the use of the internet.